1992
DOI: 10.1007/bf00052751
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of death certificates: a population-based, complete-coverage, one-year autopsy study in East Germany

Abstract: The Goerlitz Autopsy Study is a population-based autopsy study, conducted in 1987 in the municipality of Goerlitz, population 78,484, in former East Germany. It is unique in that 1,023 (96.5 percent) of the 1,060 subjects who died in the municipality over a period of one year were investigated by full autopsy. An underlying cause was assigned to every death, using the procedures recommended by the International Classification of Diseases, Injuries and Causes of Death, ninth revision, German edition. Assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1
11

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 7 publications
6
58
1
11
Order By: Relevance
“…5 These differences suggest that, similar to findings of studies examining the accuracy of death certificates in identifying respiratory and cardiovascular diseases as causes of death, hepatitis C may be underascertained among patients dying of chronic liver disease, underreported on death certificates, or both. 3,4,[13][14][15][16] In the only study to date of which we are aware that addressed this issue by comparing mortality data with medical records, the potential magnitude of underreporting of hepatitis C on death certificates was estimated to be approximately 50%. 17 If this estimate was consistent across the country, hepatitis C should have been recorded as causing approximately 9,000 (30%) CLD deaths in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…5 These differences suggest that, similar to findings of studies examining the accuracy of death certificates in identifying respiratory and cardiovascular diseases as causes of death, hepatitis C may be underascertained among patients dying of chronic liver disease, underreported on death certificates, or both. 3,4,[13][14][15][16] In the only study to date of which we are aware that addressed this issue by comparing mortality data with medical records, the potential magnitude of underreporting of hepatitis C on death certificates was estimated to be approximately 50%. 17 If this estimate was consistent across the country, hepatitis C should have been recorded as causing approximately 9,000 (30%) CLD deaths in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing international variation in death certification practices showed that individual countries in Western and Eastern Europe differ in certification and coding of underlying cause of death. [30][31][32] Thus some degree of over-and underregistration of mortality for particular amenable causes of death is likely to exist. As misclassification generates mistakes in both directions, using the aggregated measure for all selected amenable causes in the study assures less biased results.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the non-specific or erroneous ante mortem diagnosis, documented due to diagnostic error, inadequate or misinterpreted clinical information, result in the allocation of a code that may not reflect the true cause of death. This problem has been identified and confirmed in a number of studies comparing death certificate information with autopsy results or with the diagnosis of expert panels (Cameron & McGoogan 1981a & b;Kingsford 1995;Modelmog, Rahlenbeck & Trichopoulos 1992). Discrepancies between autopsy results and death certificates have been documented to be as high as 30% (Cameron & McGoogan 1981a & b).…”
Section: Resultsmentioning
confidence: 93%
“…During the last two decades many researchers have pointed out that the changes in death certification practices, disease classification and coding practices are an important factor affecting mortality statistics (Jordan & Bass 1993;Kingsford 1995;Kircher, Nelson & Burdo 1985;McKelvie 1993;Modelmog, Rahlenbeck & Trichopoulos 1992;Myers & Farquhar 1998;Nielsen, Bjornsson & Jonasson 1991;Rooney & Devis 1996;Weeramanthri & Beresford 1992;. Since IHD is the leading cause of death, it is therefore important to examine the effect of certification and classification changes on mortality trends due to IHD.…”
Section: Introductionmentioning
confidence: 99%